1992
DOI: 10.1016/s0001-2092(07)70362-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stressors and coping responses in persons with recurrent genital herpes

Abstract: Perceived stressors and coping responses in persons with recurrent genital herpes, M L Keller, R A Jadack, L F Mims Research in Nirrsing and Health Vol 14 (December 1991) 42 1–430

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…[25][26][27] However, Brookes et al,3 seeking to overcome the difficulties of such uncontrolled cross sectional designs, obtained self ratings on a variety of variables relative to before infection in long term herpes sufferers. The study had the problems of other retrospective data in this area.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] However, Brookes et al,3 seeking to overcome the difficulties of such uncontrolled cross sectional designs, obtained self ratings on a variety of variables relative to before infection in long term herpes sufferers. The study had the problems of other retrospective data in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies have shown the difficulty of patients telling significant others (e.g. family, friends) and much of their coping "taking place in isolation from supportive others" (Keller, Jadack, & Mims, 1991).…”
Section: Common Reactions As Psychotherapy Issuesmentioning
confidence: 99%
“…Keller, Jadack, & Mims, 1991) and anxiety/depression inducing issue confronting patients, since this disclosure directly exposes one's self and sexuality to the risk of (in)direct rejection, and deserves to be addressed separately. As VanderPlate and Aral (1987) note, "it is around this issue that persons must encounter the social realities of the disease and confront their own fears, insecurities, or apprehensions concerning it" (p. 63).…”
Section: The Dilemma Of Disclosing One's Hsv ‡ Status: Stigma and Feamentioning
confidence: 99%
“…The biopsychosocial burden often experienced by people living with symptomatic genital herpes has been well documented ( Keller et al 1991, Swanson & Chenitz 1993, Mindel 1996, Peto & Juel‐Jensen 1996). To alleviate the physical and psychological pain and to improve quality of life, early studies examined psycho‐social support for individuals ( Gould & Tissler 1984), couples ( Drob & Bernard 1985) and groups ( Drob & Bernard 1986, Longo et al 1988 , McLarnon & Kaloupek 1988).…”
Section: Introductionmentioning
confidence: 99%